Problem-Based Learning Application to Increase Critical Thinking Ability and Learning Result of Economic Student Learning - Putri, Desi Pramita (Unversitas Negeri Malang, 2019)
This research aims to know the implementation of the Problem Based Learning model in critical thinking skill and student learning outcome to the Economy subject in the X IIS 3 class SMA Negeri 1 Garum. The research design used was classroom action research. This research was conducted in 2 cycles. Based on research results it was known that there was an improvement of student activity in the X IIS 3. It was showed the percentage of student critical thinking skills results in cycle I for 61,3% and in cycle II is improved for 77%. The improvement of student learning outcome could be seen from the completeness of student learning outcome in the cognitive domain with the post-test average score of students that improved from cycle I for 78,64% improved to be 91,61% in the cycle II. Therefore, it could be concluded that the implementation of Problem Based Learning could critical thinking skills and student learning outcomes in the X IIS 3 SMA Negeri 1 Garum. Suggestion for teacher of Economy The subject was this model could be made as an alternative to improve critical thinking skills and student learning outcomesKeywordscritical thinking, learning outcomes, problem-based learning